2010
DOI: 10.1007/s00125-010-1738-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved insulin sensitivity, preserved beta cell function and improved whole-body glucose metabolism after low-dose growth hormone replacement therapy in adults with severe growth hormone deficiency: a pilot study

Abstract: Our data indicate that long-term low-dose growth hormone treatment may improve insulin sensitivity and whole-body glucose metabolism in adults with severe growth hormone-deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 52 publications
2
13
1
Order By: Relevance
“…Indeed, when we considered ISI, we found lower insulin sensitivity in the GHD group compared to controls, with a trend toward increase, although not statistically significant, during GHT. These data are partially in agreement with those of Arafat et al, who showed an improvement in insulin sensitivity, evaluated by the clamp, after low-dose GHT [47].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, when we considered ISI, we found lower insulin sensitivity in the GHD group compared to controls, with a trend toward increase, although not statistically significant, during GHT. These data are partially in agreement with those of Arafat et al, who showed an improvement in insulin sensitivity, evaluated by the clamp, after low-dose GHT [47].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, reduction of adipose tissue has been shown to increase insulin sensitivity and glucose tolerance 35 . With respect to grown hormone, literature data show that this hormone favorably alters the obesity profile, reducing abdominal and visceral obesity, increasing insulin sensitivity, and benefitting lipoprotein metabolism and diastolic blood pressure [36][37][38][39] . The present results agree with these reports since the MetS group had lower plasma GH concentrations than the non-MetS group.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, discordant data exist about the different metabolic effects of [31] and a larger prospective study where patients of both groups are randomized to different GH doses can give more complete information. Furthermore, the shortterm clinical and metabolic evaluation performed in this study does not allow to affirm with certainty that children with a GH peak between 8 and 10 µg/l cannot fully benefit from GH therapy and a longer follow-up would be required.…”
Section: Discussionmentioning
confidence: 99%